The Effect Of Company Size And Debt To Equity Ratio On Profitability Manufacturing Companies That Listed On The Indonesia Stock Exchange - Muhammad Fahmi Tanjung; Anggi Pratama Nasution; Yossy Fadly (Britain International for Academic Research (BIAR) Publisher, 2022)
This paper research discused about an effect of firm size and debt to equity ratio on the profitability of Manufacturing Companies Listed on the Indonesia Stock Exchange. Profitability shows the company's ability to earn a profit or a measure of the effectiveness of the company's management. The period of the company in this study was taken from 2016 until 2020. The data collection technique used in this study was by means of a documentation study. The analytical method used in this study is multiple linear regression analysis in its calculations assisted by the Statistical Package for the Sciences Social (SPSS) v. management program. 20. The results of this study partially show that the size of the company has no significant effect on profitability, while the debt-to-equity ratio has a positive and significant effect on profitability. Meanwhile, simultaneously, it shows that the size of the company and the debt-to-equity ratio have a significant effect on profitability.